Detective fiction and the metafictional strategies in James McCreet’s Neo-Victorian novels - Ababneh, Inas (Research Journal in Advanced Humanities, 2026)
The significance of this paper emanates from its endeavor to initiate the filling of the gap in the scholarship on James McCreet’s work. James McCreet (b. 1971) is a contemporary British novelist who revisits the Victorian Age in his four novels: The Incendiary’s Trail (2009), The Vice Society (2010), The Thieves’ Labyrinth (2011), and The Masked Adversary (2012. This paper clarifies that McCreet’s novels encompass both neo-Victorianism and postmodern metafiction. As historiographic metafictional novels, they subvert the notions of absolute truth and objectivity. McCreet subverts the Victorian assumptions to knowledge and truth through the parodic appropriation and reformulation of the detective plot, as manifested in the work of Edgar Allan Poe and Arthur Conan Doyle. Among the postmodern metafictional strategies that McCreet relies on are the unreliable narrator, the self-reflexive mode, intertextuality, parody, and irony. McCreet’s parodic intertextuality is essential because it allows the reader to explore, on the one hand, the power and the limitations of the traditional detective novel and on the other, the possibilities that can be gained from the reworking of the detective plot. Moreover, through installing and then subverting the nineteenth-century conventions the reader perceives many instances of irony.